Pengukuran Kinerja Pada PT. Ital Fran’s Multindo Food Industries Cabang Bali dengan Metode Balanced Scorecard - Dewi, Ni Putu Lilik Setya; Satriawan, I Ketut; Yoga, I Wayan Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 4 (2021): DesemberDO - 10.24843/JRMA.2021.v09.i04.p12, 2021)
Ital Fran's Multindo Food Industries Bali Branch is one of the companies engaged in the food processing industry that produces bread with competitive and complex business competition conditions. The purpose of this study is to determine the company's performance of PT. Ital Fran's Multindo Food Industries Bali Branch using the Balanced Scorecard (BSC) method. This research was conducted by observing the company, interviewing the company's management and distributing questionnaires to customers and employees. The results showed that the total performance score for each perspective was a financial perspective, which was 14.36%, a customer perspective was 22,91%, an internal business process perspective was 24.16% and a learning and growth perspective was 23,43%. Based on the criteria for the total score of performance appraisal shows that the company PT. Ital Fran's Multindo Food Industries Bali Branch is in "Very Healthy (AA)" condition with an overall performance score of 84,86%. Keyword: performance measurement, performance analysis , balanced scorecard perspective